Molecular Characterization of Retinoic Acid Receptor CgRAR in Pacific Oyster (Crassostrea gigas) - Jin, Kaidi; Jin, Qianqian; Cai, Zhongqiang; Huang, Baoyu; Wei, Lei; Zhang, Meiwei; Guo, Wen; Liu, Yaqiong; Wang, Xiaotong (Frontiers in Physiology, 2021)
Retinoic acid (RA) signaling pathways mediated by RA receptors (RARs) are essential for many physiological processes such as organ development, regeneration, and differentiation in animals. Recent studies reveal that RARs identified in several mollusks, including Pacific oyster Crassostrea gigas, have a different function mechanism compared with that in chordates. In this report, we identified the molecular characteristics of CgRAR to further explore the mechanism of RAR in mollusks. RT-qPCR analysis shows that CgRAR has a higher expression level in the hemocytes and gonads, indicating that CgRAR may play roles in the processes of development and metabolism. The mRNA expression level of both CgRAR and CgRXR was analyzed by RT-qPCR after injection with RA. The elevated expression of CgRAR and CgRXR was detected upon all-trans-RA (ATRA) exposure. Finally, according to the results of Yeast Two-Hybrid assay and co-immunoprecipitation analysis, CgRAR and CgRXR can interact with each other through the C-terminal region. Taken together, our results suggest that CgRAR shows a higher expression level in gonads and hemocytes. ATRA exposure up-regulates the expression of CgRAR and CgRXR. Besides, CgRAR can interact with CgRXR to form a heterodimer complex.